Self‐Assembled/Drug‐Composed Nanomedicine for Synergistic Photonic Hyperthermia and Targeted Therapy of Breast Cancer by Inhibiting ERK, AKT, and STAT3 Signaling Cascades - He, Chao; Yu, Luodan; Ding, Li; Chen, Yu; Hao, Yongqiang (Advanced functional materials, 2020)
Superior to chemotherapy, photonic hyperthermia and targeted therapy have made attractive impacts on cancer treatment by virtue of their profound advantages such as high specificity and minimal invasiveness, but the rational integration of corresponding therapeutic drugs for achieving concurrent photothermal ablation/targeted therapy is still challenging. Herein, a self‐assembled nanomedicine Anlotinib@IR820 is constructed with drug formulations for highly efficient and synergistic photonic hyperthermia and targeted therapy against breast cancer. Specifically, the constructed Anlotinib@IR820 nanomedicine presents high accumulation at the tumor site owing to the enhanced permeability and retention effect and simultaneously overcomes the obstacles of poor water solubility of Anlotinib (for targeted therapy) and the short lifetime of IR820 (for photonic ablation). The photothermal ablation as activated by near‐infrared laser can not only irradiate cancer cells but also promote the cellular uptake of Anlotinib, which presents a profound synergistic function both in vitro and in vivo. Mechanically, Anlotinib@IR820 nanomedicine can induce apoptosis and cause cell cycle arrest in breast cancer through inhibiting ERK, AKT, and STAT3 pathways. Therefore, the rationally designed drug‐composed Anlotinib@IR820 nanomedicine exhibits high clinical translation potential because of its therapeutic nanoformulation, which provides an alternative option for efficient combinational therapy of breast cancer. Herein, a self‐assembled nanomedicine Anlotinib@IR820 with drug formulations for synergistic photonic hyperthermia and targeted therapy is introduced into the treatment of breast cancer. Mechanically, the nanomedicine can induce apoptosis and cause cell cycle arrest in breast cancer by inhibiting the ERK, AKT, and STAT3 pathways that exhibit high clinical translation potential.